Influence of Leadership Model, Work Environment, and Motivation, Towards Employee Performance of Pt. Sembrani Arutala Sejati Surabaya - Rosyafah, Siti; Setyarti, Eryana; Lakshita, Dhuihitta Mahardhika (PT FORMOSA CENDEKIA GLOBAL, 2023)
Human resources play a crucial role in a company's success. Empowering them efficiently yields optimal benefits. PT. Sembrani Arutala Sejati Surabaya, a transportation company, must harness its human resources to enhance quality and customer service. Effective leadership, a conducive work environment, and motivation are essential for achieving company goals. This research investigates the impact of leadership models, work environment, and motivation on employee performance at PT. Sembrani Arutala Sejati Surabaya. Multiple linear regression and hypothesis testing (F test, t test, and dominance) are used in the study, which makes use of primary data from surveys given to employees and company leaders. The results show that motivation, the work environment, and leadership styles all have a simultaneous and substantial impact on employee performance at PT. Sembrani Arutala Sejati Surabaya.